2020
DOI: 10.1007/s11356-020-10705-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air pollution exposure during various periods of pregnancy on term birth weight: a large-sample, retrospective population-based cohort study

Abstract: Previous studies have suggested that maternal exposure to air pollution might affect term birth weight. However, the conclusions are controversial. Birth data of all term newborns born in Xi’an city of Shaanxi, China, from 2015 to 2018 and whose mother lived in Xi’an during pregnancy were selected form the Birth Registry Database. And the daily air quality data of Xi’an city was collected from Chinese Air Quality Online Monitoring and Analysis Platform. Generalized additive models (GAM) and 2-level binary logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 51 publications
3
28
0
1
Order By: Relevance
“…The majority of studies reported positive or null associations between air pollution and LBW in the 3rd trimester (Bosetti et al 2010.We observed that maternal exposures to air pollution (PM 2.5 , PM 10 , SO 2, and NO 2 ) in the 3rd pregnancy were negatively related to TLBW in single pollutant models, which were only consistent with one study (Shang et al 2021).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The majority of studies reported positive or null associations between air pollution and LBW in the 3rd trimester (Bosetti et al 2010.We observed that maternal exposures to air pollution (PM 2.5 , PM 10 , SO 2, and NO 2 ) in the 3rd pregnancy were negatively related to TLBW in single pollutant models, which were only consistent with one study (Shang et al 2021).…”
Section: Discussionsupporting
confidence: 77%
“…The associations between PM 2.5 , PM 10 , SO 2, and NO 2 exposure and TLBW/ macrosomia were stronger in women who conceived in the warm season compared with those who conceived in the cold season. A retrospective cohort study based on birth records in Guangdong province reported that O 3 exposure was associated with LBW for the babies conceived in cold season (Wang et al 2021). Wang et al found that the associations between air pollution and SGA varied by season of conception.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations